STATE IDEALISM AND THE EMERGING DEMOCRATIZATION CHALLENGES OF INDONESIA POST-POLITICAL ELECTION IN ABU NASR AL-FARABI’S PARADIGM OF QUR’ANIC EXEGESIS - Egi Tanadi Taufik (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2021)
Over 11 centuries, Abu Nasr al-Farabi (d. 950) is well-known as a great philosopher and political scientist. Few studies have examined al-Mu'allim al-Ṡani’s capacity as a Qur’anic interpreter. Even though Al-Farabi has never written a complete Qur’anic exegesis book, he is noticed consistently paraphrasing verses of the Qur’an into political statements to justify the interrelatedness between Islamic political thought with Ancient Greek’s one which inspired from Plato and Aristotle. This characteristic is seen in some of his masterpieces as Arāyat Ahl al-Madīnah al-Faḍīlah and al-Siyāsah al-Madīnah. This paper seeks the potential adaptation of al-Farabi's idea about the ideal society, based on his alteration of Qur’anic verses into political concepts, as an alternative to fulfill the shortfall of Indonesian democracy. The article reflects al-Farabi's thoughts in the context of democratization challenges in Indonesia post-political campaign and suggested that its practice of democration is still considered as a "green" and imperfect form. Keywords: Abu Nasr al-Farabi; madīnah al-fadhīlah al-sa’ādah, Democratization Challenges. Qur’anic Exegesis